THE EFFECT OF INSPIRATIONAL FILM MEDIA APPLICATION ON THE WRITING SKILLS OF EXPLANATORY TEXTS OF XIth GRADE SENIOR HIGH SCHOOL 1 HARAU ON DISTRICT 50 KOTA - _, Wangiman; Wahyuni, Neneng; Linda, Wirda; Susandra, Elsadina; Yulianti, Sonita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2024)
This reearch aims to describe the Effect of Applying Inspirational Film Media on Students' Explanatory Text Writing Skills. Type of thi research is quantitative with experimental methods. The population was XI grade students of senior high chool,with 208 students. The sample was XI grade of second social class, with 25 students and XI grade of third social clas with totaling 25 students. This research instrument used a performance test with research indicators, namely the structure of explanatory text, the language of explanatory text. Data were analyzed with the 't' test by first carrying out normality, homogeneity, and hypothesis testing. Data analysis showed that inspirational film media had an effect on learning to write explanatory texts in Indonesian subjects in the experimental class. This is evidenced by an increase in student scores, which during the pre-test the mean (X) was 67.76. After applying inspirational film media in the learning process at the time of post-test with the mean (X) is 86.76. This can be seen from the comparison between tcount and ttable (5.70 > 2.021), because tcount is greater than ttable, Ha (alternative hypothesis) is accepted. So the learning outcomes of experimental class who were taught better than the learning outcomes of control class students who were taught using conventional methods.